Talent Management for The Development of Quality Teaching Staff - Hadi, Rizal; Abd Haris; Esa Nur Wahyuni (Al-Qalam Institue, 2025)
Improvements in education quality are highly dependent on the competence of educators and educational staff, which requires effective talent management. This study aims to describe and analyze the process of identifying, developing, and retaining talent, as well as its impact on the quality of educational personnel in schools. The research method employed is a case study with a qualitative approach, utilizing interviews, observations, and documentation, which were analyzed using thematic analysis with NVivo 12 Pro. Research findings indicate that the talent identification process begins with identifying needs, followed by establishing acquisition strategies, competency-based selection, and talent mapping; talent development through training and workshops improves the performance of educators; retention efforts through appropriate incentives play a crucial role in retaining high-quality educators; and talent management contributes to the development of competencies among educators and educational staff as well as academic achievements of students. This research is important for optimizing human resource management in education.